Peningkatan Kualitas Layanan Perawat Melalui Metode Pelatihan: Improving Nurse Service Quality Through Training Methods - Yunma Yunma (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2011)
Service quality plays a crucial role in customer satisfaction. This research aims to enhance the service quality of nurses through training methods. The study design employs an untreated control group design with pretest and posttest. The experimental group consisted of 9 junior nurses, while the control group comprised 10 junior nurses. The experimental group received training on service quality, whereas the control group did not. Nurses' service quality was measured using observation rating scale sheets, with an interrater reliability coefficient of 0.77. Non-parametric Mann-Whitney U test was used for data analysis. Hypothesis testing revealed no significant differences in service quality between the experimental and control groups. Kualitas layanan memiliki peran penting dalam kepuasan pelanggan. Penelitian ini bertujuan untuk meningkatkan kualitas layanan perawat melalui metode pelatihan. Desain penelitian menggunakan untreated control group design dengan pretest dan posttest. Kelompok eksperimen terdiri dari 9 perawat junior, sedangkan kelompok kontrol terdiri dari 10 perawat junior. Kelompok eksperimen dilatih tentang kualitas layanan, sementara kelompok kontrol tidak diberikan pelatihan. Kualitas layanan perawat diukur menggunakan lembar observasi rating scale. Koefisien reliabilitas antar-pengamat adalah 0,77. Data dianalisis menggunakan uji non-parametrik Mann-Whitney U. Hasil pengujian hipotesis menunjukkan tidak ada perbedaan signifikan dalam kualitas layanan antara kelompok eksperimen dan kelompok kontrol.